Online technology of food delivery services apps, OFDS on purchase intention - Naina Mohamed, Rozita; Rusli, Mohd Saifullah; Md Jusoh, Zuroni (Malaysian Consumer and Family Economics Association MACFEA, 2022)
Nowadays, technology in food delivery online services apps is excessively used among customers in Malaysia. Moreover, it has become more and more popular worldwide. Customers are getting comfortable using app services to order their meals via their smartphones. There are more than ten online food distribution service providers currently operating in Malaysia. What separates them, though, is the speed of services, the food prices, the delivery rates, the selections deals, the user interface (UI) of the apps, user-friendliness etc. Therefore, this research is carried out to examine the key factors affecting the intention of customers to use online food delivery services among customers in Malaysia. A valid response rate of 280 was obtained using an online survey instrument. The factor impacting the purchasing intention of using online technology of food delivery services apps is the primary focus of this research on the collection of information using a probability sample method. The research investigates the most significant factors that influence the customer purchase intention on using Online Food Delivery (OFD) services apps. There are 4 independent variables which we are focusing on; time factor, price factor, convenience motivation factor and food illustration factor. The analysis and results show that the convenience shopping motivation factor is the key driver where exogenous variables influence customers' purchase intention directly. Customers would anticipate the apps they wish to use to have a beneficial impact on them in terms of convenience and new added value that they may gain when choosing the chosen online food delivery services for themselves since any new technology made is to improve the life of all humankind. If the chosen applications could provide all of the desired experiences, users would use them more regularly, resulting in consistent repeat purchases, especially for those who use online food delivery services frequently. As a result, it is critical for operators and app developers to truly understand the customers and develop and update their apps to make them as convenient as possible so that customers remain loyal to them.